Service use by older very frequent emergency department users: A retrospective cohort study. (September 2019) - Berry, D.; Street, M.; Considine, J.
Abstract: Background: Frequent Emergency Department (ED) attendance is a common occurrence, across all patient age groups. Older frequent users of ED are an at-risk group who often have complex, chronic health needs with many requiring out-of-hospital services to support their care. The aim of this study is to identify the characteristics, outcomes and health service use of older, very frequent emergency department (ED) users. Methods: A retrospective cohort study, at three Australian EDs, comparing first and last ED attendances, by older people (≥65 years) with frequent ED use (≥8 attendances/year). Results: There were 1387 ED attendances in 12 months by 115 patients (median = 11). The median age-adjusted Charlson comorbidity score increased between attendances (5 vs 6, p  < 0.001). From first to last visit, hospital stays exceeding 7 days increased (12% vs 20%, p  = 0.013), while both ED re-attendances within 28 days (58% vs 20%, p  ≤ 0.001) and hospital readmissions within 30 days (39% vs 23%, p  = 0.016) decreased. In-patient mortality was 11% ( n  = 10/88). There was no change in out-of-hospital services in place at both ED attendances (55% vs 61%, p  = 0.185). Conclusions: Out-of-hospital service use did not change despite frequent ED attendance. Older very frequent ED users had increasing co-morbidities over time and often required hospital admission.